Content validity analysis of literacy assessment instruments - Dameis Surya Anggara; Candra Abdillah (Jurnal Cakrawala Pendidikan, 2023)
This research is part of the development of teacher assessment literacy instruments. The research objective at this stage was to determine the content validity of the instrument. The instruments developed were 25 multiple-choice items constructed from Assessment Objectives, Measurement Theory, Assessment Process, and Assessment Fairness. Then the instrument is assessed qualitatively through a Focus Group Discussion to collect various suggestions and input from various points of view. After that the instrument was assessed quantitatively by 3 experts with 6 aspects of assessment, namely 1) the relevance of the item to the assessment literacy dimension, 2) relevance of items with indicators, 3) clarity of the main items, 4) logical answer options, 5) standardization of language, and 6) the functioning of descriptions/ cases/ pictures/ tables on items. The collected data were analyzed according to the type of data. Qualitative data analyzed using a qualitative approach, while quantitative data were analyzed using Conten Validity Index (CVI). The results showed that of the 25 items, each had a CVI value of more than 0.60 with an average of 0.96. So it can be concluded that the items and instruments of assessment literacy have valid criteria based on content.